FEATURES OF LASER BORATING OF PISTON RINGS - Glushkova, D.; Makovyey, R.; Ryzhkov, Yu.; Demchenko, S.; Глушкова, Д. Б.; Маковей, Р. Г.; Рижков, Ю. В.; Демченко, С. В.; Глушкова, Д. Б.; Маковей, Р. Г.; Рыжков, Ю. В.; Демченко, С. В. (Харьковский национальный автомобильно-дорожный университет, 2017)
Piston rings in the process of operation are subject to wear. Non-sufficient wear resistance of piston ring materials often limits the growth of productivity of machines and the timing of their operation. Use of laser heating at boriding provides the formation of a new layer with special properties. The research results can be extended to other parts subject to intensive wear.
ОСОБЛИВОСТІ ЛАЗЕРНОГО БОРУВАННЯ ПОРШНЕВИХ КІЛЕЦЬ
ОСОБЕННОСТИ ЛАЗЕРНОГО БОРИРОВАНИЯ ПОРШНЕВЫХ КОЛЕЦ
Keywords: piston rings; borated layer; laser heating; поршневі кільця; шар борування; лазерне нагрівання; поршневые кольца; борированный слой; лазерный нагрев; 621.793